(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Mahmud al-Kashgari, a man of great erudition and talent for his time, created a unique, unparalleled dictionary, which has become one of the most valuable monuments of culture and history of the Turkic peoples. Modern Oriental studies, including Arabic studies and Turkology are unthinkable without this work. Turkologists consider this work to be the first comparative historical study that was more than seven centuries ahead of its time. In it they find a prototype of methodological principles that were established in science only in the 20th century. It is quite in demand in the contemporary reading environment. "Devonu lugatut turk" ("Dictionary of Turkish dialects") is Mahmud Koshgari’s encyclopedic work on Turkic languages (1071-72). This work contains valuable information about Turkic clans and tribes that lived in Central Asia and Western China in the second half of the 11th century, their social status, language, history, geography, metrology and astronomy of this area.